Microwave-Assisted Green Synthesis and Characterization of Silver Nanoparticles Using Melia azedarach for the Management of Fusarium Wilt in Tomato - Ashraf, Hina; Anjum, Tehmina; Riaz, Saira; Naseem, Shahzad (Frontiers in Microbiology, 2020)
These days research in agriculture is focusing the theme of sustainability along with protection of agriculture produce. Nanotechnology in agriculture sector aims enhancement of agricultural produce and reduction of pesticides through providing innovative agrochemical agents and their novel delivery mechanisms. Current investigation involved green synthesis of silver nanoparticles from aqueous leaf extract of Melia azedarach by following microwave assisted method to control Fusarium oxysporum the causal agent of tomato wilt. Biosynthesized Melia Leaf Extract (MLE)-AgNPs were characterized by UV-visible spectroscopy, FTIR, XRD, EDX, DLS, SEM, TEM and Zeta Potential analysis. The intensity of the peak at 434nm in UV-Vis spectra, attributed to the surface plasmon resonance of MLE-AgNPs changes with reaction parameters. TEM exhibits spherical shaped nanoparticles with an average particle size ranges from 12-46 nm. Efficient inhibition of Fusarium oxysporum, the causal agent of tomato wilt was achieved after exposure to MLE-AgNPs both in-vivo and in-vitro. In-vitro studies exhibited repressed fungal mycelial growth with 79-98% inhibition as compared to the control. Significant increase in growth parameters of tomato seedlings were observed after treatment with biosynthesised nanoparticles as compared to F. oxysporum infected plants grown without them under greenhouse conditions. Furthermore, SEM imagining was done to reveal the prominent damage on cell wall of hyphae and spores after MLE-AgNPs treatment. Propidium Iodide (PI) staining of mycelium indicated extend of cell death, causing irretrievable damage and disintegration of cellular membranes by altering the membrane permeability. Also, DCFH-DA fluorescence specifies intracellular ROS production in F. oxysporum after treatment with MLE-AgNPs. Current investigation suggested that biosynthesized nanoparticles can revolutionize the field of plant pathology by introducing environment friendly approach for disease management and playing a potential part in agriculture industry. However, till today small number of works had been done to integrate nanotechnology into phyto-pathology so, the challenge to reduce the global food production, this area of research is in need to be adopted and explored for the management of plant diseases.